025 Croydon neurology: 5 years of novel service developments. Issue 9 (12th August 2022) - Nitkunan, Arani; Bagtas, Creselda; Boodhoo, Ajay; Grant, Charmaine; Lastrilla, Glenda; MacDonald, Bridget; Mastrolilli, Francesca; Rashid, Waqar; Southam, Medina; Schon, Fred
Abstract : 5 years ago we embarked on a series of novel developments to improve our DGH neurology services. The key was ever closer integrated working between consultant neurologists and specialist nurses with support from our Trust and commissioners. We highlight 6 very diverse ongoing projects: 1. Acute neurology ward referrals have increased by 49% between 2016-2021 with nurses triaging referrals prior to consultant review. 2. Post discharge nurse telephone review for selected patients since 2020 to try and reduce readmission rates. 3. Consultant delivered helpline for all local GPs Monday to Friday since 2020 to discuss urgent cases of concern. 4. Nurse delivered lumbar puncture service, since 2019 138 procedures carried out. 5. Diagnostic coding for all neurology outpatients started in 2021. Within 8 months all 5 consultants were coding over 70% of attendances. 6. Patient initiated follow up (PIFU) – 2020 NHS England initiative. Specialist nurse Helpline for patients with epilepsy, multiple sclerosis and Parkinson's running successfully since 2018. Service improvements need not be expensive or onerous but require imagination and team cohesion. We strongly recommend others to try what seems most appropriate to their service.